Chiral tubule self-assembly from an achiral diynoic lipid - Pakhomov, Serhii (The National Academy of Sciences, 2003)
Tubules possessing μm-scale chiral substructure self-assemble from an achiral isomer of the tubule-forming diynoic phosphatidylcholine, 1,2-bis(10,12-tricosadiynoyl)sn-glycero-3-phosphocholine [DC(8,9)PC], showing that molecular chirality is not essential for tubule formation. CD spectroscopy shows that these structures' helical sense of handedness instead originates in a spontaneous cooperative chiral symmetry-breaking process. We conclude that the chiral symmetry-breaking must originate in the unusual feature common to the chiral and achiral tubule-forming molecules, the diynes centered in their hydrocarbon tails.